Balthasar and the Eclipse of Nietzsche - O'Regan, Cyril (Modern theology, 2019)
This essay is about Hans Urs von Balthasar's critical appropriation of Nietzsche as a prophetic and apocalyptic thinker whose thought presents a challenge to a tired European culture and a petrified form of Christianity. But it is also about a particular expiration date for this critical appropriation which can be dated to the 1940s. The bulk of the essay deals with two early texts of Balthasar in which Nietzsche is a dominant figure, that is, Balthasar's dissertation, Geschichte des eschatologischen Problems in der modernen Literatur (1928) and Apokalypse der deutschen Seele (1939). The centrality of Nietzsche in these texts makes it all the more shocking that by the mid 1940s Balthasar's engagement has essentially come to an end. The hypothesis put forward is not that the questions raised by Nietzsche have ceased to have pertinence, but that Heidegger, who had also from the beginning been an important figure for Balthasar, essentially takes over Nietzsche's apocalyptic provocation and thereby eclipses him. Thereafter, Heidegger becomes not only the emblem of the best that Phenomenology can do, but also of a form of Nietzschianism that is more subtle and complex in its negotiations with Christianity and precisely for that reason more dangerous.